Morphology determines conductivity and seebeck coefficient in conjugated polymer blends - Zuo, Guangzheng; Liu, Xianjie; Fahlman, Mats; Kemerink, Martijn (ACS applied materials & interfaces, 2018)
The impact of nanoscale morphology on conductivity and Seebeck coefficient in p-type doped all-polymer blend systems is investigated. For a strongly phase separated system (P3HT:PTB7), we achieve a Seebeck coefficient that peaks at S ∼ 1100 μV/K with conductivity σ ∼ 3 × 10-3 S/cm for 90% PTB7. In marked contrast, for well-mixed systems (P3HT:PTB7 with 5% diiodooctane (DIO), P3HT:PCPDTBT), we find an almost constant S ∼ 140 μV/K and σ ∼ 1 S/cm despite the energy levels being (virtually) identical in both cases. The results are interpreted in terms of a variable range hopping (VRH) model where a peak in S and a minimum in σ arise when the percolation pathway contains both host and guest sites, in which the latter acts as energetic trap. For well-mixed blends of the investigated compositions, VRH enables percolation pathways that only involve isolated guest sites, whereas the large distance between guest clusters in phase-separated blends enforces (energetically unfavorable) hops via the host. The experimentally observed trends are in good agreement with the results of atomistic kinetic Monte Carlo simulations accounting for the differences in nanoscale morphology.